Determinación de contaminación sonora por fuentes móviles en la avenida 25 de junio de la ciudad de Machala - Montesdioca Guerrero, Jairo David (2018)
Noise has become an environmental problem in cities, causing diseases from stress, to heart attacks, so the general objective was to determine the levels of noise pollution produced by mobile sources on Avenida 25 de Junio. The present investigation was descriptive-correlational, a designer with a quantitative approach to data analysis. The record of the measurements was made according to LIBRO VI ANEXO 5 of the TULSMA, the monitoring of the levels of equivalent continuous noise was made in 6 points covering an extension of 1.5 km considering the hours of greatest vehicular influx comprising three intervals 07h00-09h00; 12h00-14h00; 17h00-18h00, using as instrument a Class 2 Integrating Sound Level meter, using a measurement effort of 20 minutes, located at a distance of 3 m from walls, configuring it to a response interval of 0.1 sec with the weighting filter in A and SLOW response time. For the elaboration of the sound map, the ARCGIS software was used, which facilitates the concatenation of the equivalent continuous noise values with the monitoring points, allowing the construction of isophonic ranges that were represented by colors according to their intensity. The results obtained in the sound map reflect equivalent continuous noise levels that surpass those stipulated in the regulations, with points 1 and 5 having the highest levels of equivalent continuous noise with values between 73.28 dBA and 69.94 dBA. For this the proposal was aimed at vehicular training, installation of signage and a noise monitoring system, improving drivers' vehicular culture and obtaining real-time data on sound pressure, committing the Decentralized Autonomous Government of Machala to create a map of sound on the urban helmet of the city and ordinances. Noise has become an environmental problem in cities, causing diseases from stress, to heart attacks, so the general objective was to determine the levels of noise pollution produced by mobile sources on Avenida 25 de Junio. The present investigation was descriptive-correlational, a designer with a quantitative approach to data analysis. The record of the measurements was made according to LIBRO VI ANEXO 5 of the TULSMA, the monitoring of the levels of equivalent continuous noise was made in 6 points covering an extension of 1.5 km considering the hours of greatest vehicular influx comprising three intervals 07h00-09h00; 12h00-14h00; 17h00-18h00, using as instrument a Class 2 Integrating Sound Level meter, using a measurement effort of 20 minutes, located at a distance of 3 m from walls, configuring it to a response interval of 0.1 sec with the weighting filter in A and SLOW response time. For the elaboration of the sound map, the ARCGIS software was used, which facilitates the concatenation of the equivalent continuous noise values with the monitoring points, allowing the construction of isophonic ranges that were represented by colors according to their intensity. The results obtained in the sound map reflect equivalent continuous noise levels that surpass those stipulated in the regulations, with points 1 and 5 having the highest levels of equivalent continuous noise with values between 73.28 dBA and 69.94 dBA. For this the proposal was aimed at vehicular training, installation of signage and a noise monitoring system, improving drivers' vehicular culture and obtaining real-time data on sound pressure, committing the Decentralized Autonomous Government of Machala to create a map of sound on the urban helmet of the city and ordinances.